Nitrate availability affects denitrification in Phragmites australis sediments. Issue 1 (15th January 2020) - Soana, Elisa; Gavioli, Anna; Vincenzi, Fabio; Fano, Elisa Anna; Castaldelli, Giuseppe
Abstract: Understanding relationships between an increase in nitrate (NO3 − ) loading and the corresponding effects of wetland vegetation on denitrification is essential to designing, restoring, and managing wetlands and canals to maximize their effectiveness as buffers against eutrophication. Although Phragmites australis (Cav.) Trin. ex Steud. is frequently used to remediate nitrogen (N) pollution, no information is available on how NO3 − concentration may affect plant‐mediated denitrification. In the present study, denitrification was measured in outdoor vegetated and unvegetated mesocosms incubated in both summer and winter. After spiking the mesocosms with NO3 − concentrations typical of agricultural drainage water (0.7−11.2 mg N L −1 ), denitrification was quantified by the simultaneous measurement of NO3 − consumption and dinitrogen gas (N2 ) production. Although denitrification rates varied with vegetation presence and season, NO3 − availability exerted a significant positive effect on the process. Vegetated sediments were more efficient than bare sediments in adapting their mitigation potential to an increase in NO3 −, by yielding a one‐order‐of‐magnitude increase in NO3 − removal rates, under both summer (743−6007 mg N m −2 d −1 ) and winter (43−302 mg N m −2 d −1 ) conditions along the NO3 − gradient. Denitrification was the dominant sink for water NO3 − in winter and only for vegetated sediments in summer. Nitrification likely contributed to fuel denitrification in summer unvegetated sediments. Since denitrification rates followed Michaelis–Menten kinetics, P. australis ‐mediated depuration may be considered optimal up to 5.0 mg N L −1 . The present outcomes provide experimentally supported evidence that restoration with P. australis can work as a cost‐effective means of improving water quality in agricultural watersheds.